Attitudes and Habits of Highly Humanistic Surgeons: A Single-Institution, Mixed-Methods Study. (July 2019) - Swendiman, Robert A.; Marcaccio, Christina L.; Han, Jason; Hoffman, Daniel I.; Weiner, Timothy M.; Nance, Michael L.; Chou, Carol M.
Abstract : Purpose: Humanism in medicine is associated with increased patient satisfaction, trust of patients in their doctors, and better outcomes. The authors sought to identify attitudes, habits, and other factors that sustain humanism in academic surgical faculty, and compare these with attributes determined from a previous study of internal medicine faculty. Method: A mixed-methods study design at University of Pennsylvania Health System was employed from 2016 to 2018 using a survey instrument and semistructured interviews. Surgical residents nominated faculty who exemplified humanism. In-depth interviews were then conducted with surgeons receiving the most nominations. The interviews were transcribed, and common themes were identified using the grounded theory method. These were compared with findings from a previous internal medicine study. Results: Ten faculty described three strongly shared attitudes: humility, responsibility, and a desire to live up to a high standard of professional behavior. Five habits were found important to sustaining these attitudes and their practice: self-reflection, finding deep connections with patients, maintaining personal and professional relationships, "having fun" at work, and paying it forward to surgical trainees. Surgeons also cited the importance of past role models in developing humanistic attitudes and sustaining practice. Responses were compared with previously documented attitudes and habits of humanistic internal medicine faculty at the institution. Conclusions: This study identified recurring attitudes and habits that characterize humanistic behaviors in a cohort of academic surgeons. Learning from these exemplary humanistic surgeons may inform the development of future educational programs for residents and faculty in sustaining humanism. Abstract : Supplemental Digital Content is available in the text.